2010
DOI: 10.3354/ab00245
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in cell and tissue-level biomarkers in Mytilus galloprovincialis: relevance for long-term pollution monitoring

Abstract: Mussels Mytilus galloprovincialis were collected monthly in 2 localities in the Northern Iberian Peninsula, Oia (Galicia) and Mundaka (Basque Coast), from April 2005 to May 2006, to investigate whether seasonal variability in biomarkers follows the same pattern at both geographical areas. The following battery of biomarkers was analysed: lysosomal membrane stability and structural changes, intracellular neutral lipid accumulation, cell type composition in the digestive gland epithelium, structural changes of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 54 publications
6
43
1
7
Order By: Relevance
“…This study showed the same reproductive pattern as mussels from previous studies in the SE Bay of Biscay (Ortiz-Zarragoitia et al 2011;Ortiz-Zarragoitia and Cajaraville 2010;Garmendia et al 2010;Cuevas et al 2015). Using stereological data from the present study, it can be concluded that animals undergo gametogenesis during winter months, deriving energy from stored reserves, as described by Pipe (1987).…”
Section: Influence Of Environmental Conditions On the Reproductive Cyclesupporting
confidence: 87%
See 2 more Smart Citations
“…This study showed the same reproductive pattern as mussels from previous studies in the SE Bay of Biscay (Ortiz-Zarragoitia et al 2011;Ortiz-Zarragoitia and Cajaraville 2010;Garmendia et al 2010;Cuevas et al 2015). Using stereological data from the present study, it can be concluded that animals undergo gametogenesis during winter months, deriving energy from stored reserves, as described by Pipe (1987).…”
Section: Influence Of Environmental Conditions On the Reproductive Cyclesupporting
confidence: 87%
“…This year-to-year variability among abiotic factors create variability in the gonad cycle of individuals of the same site (Seed 1976;Ferrán 1992) and as a result fall spawning may occur some years (Andreu 1958;Aguirre 1979;Villalba 1995). A second spawning peak has been described previously in the fall in mussels from the Basque coast (Garmendia et al 2010;Múgica et al 2015). The second spawning period observed in Bidasoa estuary during the fall of 2010, may also be related to the high presence of spawning individuals analyzed throughout both studied years (Fig.…”
Section: Influence Of Environmental Conditions On the Reproductive Cyclementioning
confidence: 94%
See 1 more Smart Citation
“…In the present study mussels were harvested in July along the north Spanish coast. There is a high likelihood that previous poor environmental conditions (Prato et al 2010) or post-spawning stages (Garmendia et al 2010;Ortiz-Zarragoitia et al 2011;Múgica et al 2015;Cuevas et al 2015) may have affected mussels' fatty acids composition in summer.…”
Section: Sensory Evaluation/consumer Testingmentioning
confidence: 99%
“…Gills are also an important indicator of pollution in aquatic systems, and histopathological changes have been used as biomarkers in fish exposed to contaminants (Abel 1976;Mazon et al 2002;Garmendia et al 2010). Alterations in the gill epithelium are a result of a variety of contaminant exposures, with the severity of changes depending on the pollutant concentration and exposure period (Franchini et al 1994;Evans et al 2005).…”
Section: Introductionmentioning
confidence: 99%